Nociception-Dependent CCL21 Induces Dorsal Root Ganglia Axonal Growth via CCR7-ERK Activation - Mesquida-Veny, Francina; Martínez-Torres, Sara; Del Rio, Jose Antonio; Hervera, Arnau (Frontiers in Immunology, 2022)
While chemokines were originally described for their ability to induce cell migration, many studies show how these proteins also take part in many other cell functions, acting as adaptable messengers in the communication between a diversity of cell types. In the nervous system, chemokines participate both in physiological and pathological processes, and while their expression is often described on glial and immune cells, growing evidence describe the expression of chemokines and their receptors in neurons, highlighting their potential in auto- and paracrine signalling. In this study we analysed the role of nociception in the neuronal chemokinome, and in turn their role in axonal growth. We found that stimulating TRPV1+ nociceptors induce a transient increase in CCL21. Interestingly we also found that CCL21 enhances neurite growth of large diameter proprioceptors in vitro. Consistent with this, we show that proprioceptors express the CCL21 receptor CCR7, and a CCR7 neutralizing antibody dose-dependently attenuates CCL21-induced neurite outgrowth. Mechanistically, we found that CCL21 binds locally to its receptor CCR7 at the growth cone, activating the downstream MEK-ERK pathway, that in turn activates N-WASP, triggering actin filament ramification in the growth cone, resulting in increased axonal growth.